Pengembangan Model Pembelajaran Nomor Lempar Berbasis Permainan di Sekolah Dasar: (The delevelopment of Number Through Learning Model Game-Based in Primary Schools) - Sari, Afriana; Sukirno, Sukirno; Waluyo, Waluyo (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2020)
This development research aims to produce a learning model for game-based or turbo-based learning that can improve students' motivation and ability in the basic motion of throwing numbers.Stages of teaching material development conducted by researchers based on the stages of research development or development research. The results of the validation at the small group stage regarding the quality of the learning model have entered into the "valid" criteria of the validation that is filled out by the validator obtained an average value of 3.85 and a tcount of 10.172 with a 2.262 table then a tcount of 10.172> a table of 2.262. In the validation test of a large group stated "Valid" with an average value of 4.15 and obtained the tcount of 16.397 with a ttable obtained is 2.66 the results of this analysis are tcount of 16.379> ttable 2.66 so it was concluded that the learning model developed influential in increasing students' abilities in turbo or throwing athletic activities. As well as the results obtained 82% feasible in small groups and 84.8% feasible in large groups when conducting guttman test for the results of the questionnaire given to students. From these results it can be stated that the developed learning model in throwing or turbo numbers learning based games is valid, practical, and efficient so that it can be used in athletic learning throwing numbers in primary schools. Abstrak. Penelitian pengembangan ini bertujuan menghasilkan model pembelajaran pada pembelajaran nomor lempar atau turbo berbasis permainan yang dapat meningkatkan motivasi dan kemampuan siswa pada gerak dasar nomor lempar. Tahapan pengembangan bahan ajar yang dilakukan peneliti berdasarkan tahapan penelitian pengembangan atau development research. Didapat hasil validasi pada tahap small group mengenai kualitas model pembelajaran telah masuk kedalam kriteria â€œvalidâ€Â  dari validasi yang diisi oleh validator tersebut didapatkan nilai rata-rata 3,85 dan thitung sebesar 10,172 dengan ttabel 2,262 dengan demikian thitung Â 10,172 > ttabel 2,262. Pada uji validasi dari kelompok besar dinyatakan â€œValidâ€dengan nilai rata-rata 4,15 serta didapatkan hasil thitung sebesar 16,379 Â dengan ttabel yang didapatkan adalah 2,66 hasil analisa ini adalah thitung 16,379 Â > ttabel 2,66 sehingga disimpulkan bahwa model pembelajaran yang dikembangkan berpengaruh dalam peningkatan kemampuan peserta didikÂ  dalam aktivitas atletik turbo atau lempar. Serta didapatkan hasil 82% layak pada kelompok kecil dan 84,8% layak pada kelompok besar saat melakukan uji guttman untuk hasil angket yang diberikan kepada peserta didik. Berdasarkan hasil ini dapat dinyatakan bahwa model pembelajaran nomor lempar yang dikembangkan valid, praktis, dan efisien sehingga dapat di gunakan pada pembelajaran atletik nomor lempar di sekolah dasar.